Further studies on splenectomy techniques in equine(donkeys) : An experimental study - Ibrahim Abdallah Emam Ahmed; Haitham Ali Farghali; Sayed Tawfik Elzomor (Cairo : Ibrahim Abdallah Emam Ahmed, 2018)
In the present study encompassed of twenty one experimental donkeys that divided into 2 main groups: group one for partial splenectomy and group two for total splenectomy. Group 1 and group 2 were sub divided to 3 subgroups and 4 subgroups respectively 3 animals for each technique. Partial splenectomy was performed after partial resection of 15th ,16th and 17th ribs and total splenectomy performed after partial resection of 16th and 17th ribs either in standing or recumbent position. Regarding splenectomy in standing postion splenectomy after resection of the 17th rib was better than that of the 16th rib. Resection of the 16th and 17th ribs were found suitable and easy for performance in case of recumbency, where 16th rib approach was more convenient. All over the techniques, the cut ribs have kept without total removal while the severed bone could be kept intact a fact which is considered a new idea in case of partial and total removal of the spleen. Total Splenectomy following resection of the 17th rib in the standing position was better than that performed in lateral recumbency and after resection of the 16th rib in standing position. partial splenectomy after partial resection of the 16th rib was the most appropriate method for partial splenectomy
Thesis (Ph.D.) - Cairo University - Faculty of Veterinary Medicine - Department of Surgery - Anaesthesiology - Radiology
Issued also as CD
Keywords: Doppler; Rib; Splenectomy